1994
DOI: 10.1111/j.1471-6402.1994.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Placing Premenstrual Syndrome in Perspective

Abstract: In a longitudinal prospective study, mood fluctuations were assessed for evidence of premenstrual syndrome (PMS) as well as other menstrual, day of week, and lunar cyclicity. Volunteer participants from the cornmunity (60 women and 10 men) provided daily data for 12 to 18 weeks. Significant mood fluctuation was determined by a new nonparametric method using each individual's own standard deviation as a measure of "marked" change. Cyclicity was the norm; two thirds of both the women and men had one or more mens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
2
15
0
1
Order By: Relevance
“…Many gather data for only 1 MC, which does not capture cycle-to-cycle variation [10]. Culturally generated expectations can bias reporting; women socialized to expect premenstrual distress are primed to report increased problems during that phase [6,11,12]. Methodologies designed to minimize this bias are: (i) to collect information prospectively, (ii) to obscure the menstrual focus of the research, (iii) to offer a range of mood items for study such as increased energy or positive (happy) mood as well as depression/irritability and (iv) to include all MC phases for comparison with the premenstruum; if only some phases are studied, it is not possible to conclude that the premenstruum has the worst moods.…”
Section: Introductionmentioning
confidence: 99%
“…Many gather data for only 1 MC, which does not capture cycle-to-cycle variation [10]. Culturally generated expectations can bias reporting; women socialized to expect premenstrual distress are primed to report increased problems during that phase [6,11,12]. Methodologies designed to minimize this bias are: (i) to collect information prospectively, (ii) to obscure the menstrual focus of the research, (iii) to offer a range of mood items for study such as increased energy or positive (happy) mood as well as depression/irritability and (iv) to include all MC phases for comparison with the premenstruum; if only some phases are studied, it is not possible to conclude that the premenstruum has the worst moods.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the incidence was even higher (67%). Self-diagnosis of PMS was even more prevalent in this college sample 300 H. Smith and S. P. Thomas (89%) than in a community sample of 60 women studied by McFarlane and Williams (1994). In that study, 51.7% of participants said they had PMS, although only 11.7 % met the researchers' "conservative criteria" and only 6.7% had both self-and researcher-designated PMS.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, this sample of women reported an increase in non-pathological anxiety, depressive, and obsessive-compulsive symptoms; somatization; neuroticism; and interpersonal sensitivity in the premenstrual versus the follicular phase (Gonda et al, 2008), suggesting that even healthy women experience a consistent fluctuation of affect across the menstrual cycle. However, some prospective studies following the same women over time have found little evidence for a consistent pattern of negative premenstrual symptom worsening as compared to other cycle phases, despite the fact that many of these women reported experiencing premenstrual syndrome in retrospective reports (Hardie, 1997; McFarlane and Williams, 1994). This highlights the importance of using prospective symptom tracking to identify menstrual cycle-related changes.…”
Section: Psychopathology Related To the Menstrual Cyclementioning
confidence: 97%